Nanopartículas auto-organizadas de goma de cajueiro (Anacardium occidentale L.) hidrofobizada para o desenvolvimento de sistemas de carreamento de fármacos - Cardial, Mayrla Rocha Lima (2019)
In this work we produced self-organized nanoparticles and Pickering emulsions for drug loading. In a first stage, the reaction conditions for the production of acetylated cashew gum with different degrees of substitution were inverted through factorial planning. Subsequently, we investigated the formation of self-organized nanoparticles from different derivatives obtained and the influence of the degree of acetylation and salt concentration added on the properties of the Pickering emulsions. Finally, formulations of self-organizing systems containing amphotericin B (AmB) and Pickering emulsions for incorporation of indomethacin (IND) were produced. Statistical analysis ANOVA and linear regression showed that the different derivatives had both the yield and the degree of acetylation influenced by the temperature and by an interaction effect between the time and quantity of acetylating agent. The applied methodology allowed to identify good reactional conditions, which led to the production of acetylated derivatives with superior yield of up to 97% and degree of acetylation 3. The self-organized systems formed had particle sizes between approximately 160 and 340 nm. Amphotericin-B release profiles incorporated into derivative nanoparticles, GCAA1-AmB stood out with 72% encapsulation efficiency and prolonged release profile, within 72 h. The obtained emulsions presented droplet sizes in the range of 269 to 312 nm, with a unimodal size distribution and zeta potential values of -46 to -48 mV. The encapsulation efficiencies were in the range of 26 to 52%, a constant release profile achieved in 3 h, releasing the maximum of 75% IND. In view of the above, it was shown that the proposed chemical modification was effective and presented promising results in the encapsulation of hydrophobic active principles by different methods.